Validation of a rubric to assess innovation competence - Frances Watts; Juan A. Marin-Garcia; Amparo García Carbonell; Lourdes E. Aznar-Mas (WPOM : Working Papers on Operations Management)
This paper addresses the development and validation of rubrics, materials and situations for the assessment of innovation competence. Research was carried out to verify the viability of the first draft of the assessment criteria, which led to refinement of the criteria and proposals to enhance the ensuing validation process that will include students and raters of different language backgrounds.